2015
DOI: 10.1007/s00405-015-3769-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-allergic rhinitis with eosinophilia syndrome is not associated with local production of specific IgE in nasal mucosa

Abstract: Non-allergic rhinitis with eosinophilia syndrome (NARES) is an eosinophilic inflammation of the nasal mucosa without evidence of an allergy or other nasal pathologies. Patients complain about perennial symptoms like nasal obstruction, rhinorrhea, itchiness and sneezing of the nose sometimes accompanied by hyposmia. The aim of the study was to better characterize NARES patients using immunoassay-biochip technology to examine serum and nasal secretion. Sera and nasal secretion of patients with NARES (perennial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 30 publications
1
36
0
4
Order By: Relevance
“…10 Some patients with authentic NAR, who really do not have allergen-specific IgE, even show nasal infiltration of inflammatory cells. [12][13][14][15] This NAR with inflammation can be further classified into differential subtypes, such as NAR with eosinophilia syndrome or NAR with neutrophils, on the basis of infiltrating cell types. [12][13][14][15] Among them, our mouse model best resembled NAR with eosinophilia syndrome: nasal eosinophilic inflammation with IgE-independent rhinitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Some patients with authentic NAR, who really do not have allergen-specific IgE, even show nasal infiltration of inflammatory cells. [12][13][14][15] This NAR with inflammation can be further classified into differential subtypes, such as NAR with eosinophilia syndrome or NAR with neutrophils, on the basis of infiltrating cell types. [12][13][14][15] Among them, our mouse model best resembled NAR with eosinophilia syndrome: nasal eosinophilic inflammation with IgE-independent rhinitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although NAR is not considered an allergy, some patients with NAR show nasal infiltration of inflammatory cells including neutrophils, eosinophils, and mast cells that suggests local activation of innate and/or adaptive immunity. [12][13][14][15] In addition, histamine, a major mediator of type 1 allergic reactions, is involved in the disease symptoms, because antihistamines are often effective in patients with NAR. 11 Thus, the nasal symptoms of NAR with inflammation might be an immune-mediated hypersensitivity reaction.…”
mentioning
confidence: 99%
“…ECP levels in nasal secretions can be used to monitor eosinophilic inflammation in different kinds of rhinitis with eosinophilic involvement, and they constitute an indicator of the efficacy of treatment [44]. NARES is not associated with local allergy (entopy) nor with a local inflammation driven by Staphylococcus aureus enterotoxin [45].…”
Section: Nonallergic Rhinitis With Eosinophilia Syndromementioning
confidence: 99%
“…Under this limited perspective, all the other variants of NAR could be defined as non-NARES. Actually, nasal cytology suggested that the situation is more complex than two variants of NAR[73]; moreover, very recent evidences suggested that also NARES might recognize immunological mechanisms other than entopy[74]. Gelardi et al[73] described at least four cytological patterns of NAR (Figure 1): (1) NAR with eosinophils (NARES); (2) NAR with mast cells (NARMA); (3) NAR with neutrophils (NARNE); and (4) NAR with eosinophils and mast cells (NARESMA).…”
Section: Nasal Cytologymentioning
confidence: 99%